PENINGKATAN HASIL BELAJAR MATERI BANGUN DATAR MENGGUNAKAN MODEL DISCOVERY LEARNING BERBANTUAN WORDWALL DI KELAS IV SDN 141/III SELAMPAUNG KABUPATEN KERINCI - Fitri, Salgia; Andika, Refiona; Ahmad, Syafri; Salmaini, Salmaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research emerged because student learning achievement was still low, at 22.22% in the flat shapes material in elementary school mathematics. This data was obtained from observation and pre-test at SDN 141/III Selampaung. This study aimed to explain how to develop a deep learning design, implement the learning process, and improve student learning outcomes in flat shapes material. This research employed the Discovery Learning model assisted by Wordwall in grade IV at SDN 141/III Selampaung, Kerinci District. This study was a Classroom Action Research (CAR) that used qualitative and quantitative approaches. The research was conducted over two cycles. Each cycle included planning, action implementation, observation, and reflection. The research subjects consisted of 14 grade IV students. Data were collected through observation, tests, and documentation. The data were then analyzed using qualitative and quantitative data analysis. The research results showed an increase in student learning outcomes in each cycle. Attitude: achievement increased from 73.15% in cycle I to 82.6% (B) in cycle II. Skills: achievement increased from 68.7% in cycle I to 81.4% (B) in cycle II. Knowledge: the average student score increased from 70.4% in cycle I to 88.9% (SB) in cycle II, and the percentage of student learning mastery increased in each cycle. Based on these findings, it can be concluded: the application of the Discovery Learning model assisted by Wordwall was effective. The application of the Discovery Learning model assisted by Wordwall improved student learning outcomes in flat shapes material in grade IV elementary school.